The effect of the timing and spacing of births on the level of labor market involvement of married women - Kenneth R. Troske; Alexandru Voicu (Institute for the Study of Labor (IZA), 2009)
We use panel data from NLSY79 to analyze the effects of the timing and spacing of births on the labor supply of married women in a framework that accounts for the endogeneity of labor market and fertility decisions, the heterogeneity of the effects of children and their correlation with the fertility decisions, and the correlation of sequential labor market decisions. Our results show that timing and spacing of births are important determinants of the effect of children on women's labor supply. Delaying the first birth leads to higher levels of labor market involvement before the birth of the first child and reduces the negative effect of the first child on the level of labor market involvement. Having the second birth after a longer interval reduces the effect of the second child on participation but increases its effect on the probability of working full time, as more women, having returned to work, respond to the second birth by moving from full time to part time jobs. Individual heterogeneity plays an important role in the relationship between labor market and fertility decisions. Women who have fewer children have the first birth later in life and space subsequent births more closely together, work more before the birth of the first child, but face larger effects of children on their labor supply.
urn:nbn:de:101:1-200910122584
Keywords: C11; C15; J13; J22; 330; Timing and spacing of births; female labor supply; endogenous fertility decisions; heterogeneous children effects; multinomial probit model; Gibbs sampler; Frauenerwerbstätigkeit; Arbeitsangebot; Fruchtbarkeit; Mütter; Zeitallokation; USA